2020
DOI: 10.1093/mnras/staa546
|View full text |Cite
|
Sign up to set email alerts
|

Into the Ly α jungle: exploring the circumgalactic medium of galaxies at z ∼ 4−5 with MUSE

Abstract: We present a study of the galaxy environment of 9 strong H i+C iv absorption line systems (16.2 < log(N(HI)) < 21.2) spanning a wide range in metallicity at z ∼ 4 − 5, using MUSE integral field and X-Shooter spectroscopic data collected in a z ≈ 5.26 quasar field. We identify galaxies within a 250 kpc and ±1000 km s −1 window for 6 out of the 9 absorption systems, with 2 of the absorption line systems showing multiple associated galaxies within the MUSE field of view. The space density of Lyα emitting galaxies… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 147 publications
(185 reference statements)
0
18
0
1
Order By: Relevance
“…At the lowest redshift, Cai et al (2019) used the Keck Cosmic Web Imager (KCWI) to observe a sample of z ∼ 2.3 quasars. At higher redshift, observations have been carried out with MUSE in a few individual quasar fields at z ≈ 5 (Ginolfi et al 2018;Bielby et al 2020;Drake et al 2020) and in a sample of 31 quasars at z ∼ 6.3 (Farina et al 2019). The median profiles from these surveys are shown with dashed lines in the right-hand panel of Fig.…”
Section: The Radial Profile Of the Extended Ly α Emissionmentioning
confidence: 99%
“…At the lowest redshift, Cai et al (2019) used the Keck Cosmic Web Imager (KCWI) to observe a sample of z ∼ 2.3 quasars. At higher redshift, observations have been carried out with MUSE in a few individual quasar fields at z ≈ 5 (Ginolfi et al 2018;Bielby et al 2020;Drake et al 2020) and in a sample of 31 quasars at z ∼ 6.3 (Farina et al 2019). The median profiles from these surveys are shown with dashed lines in the right-hand panel of Fig.…”
Section: The Radial Profile Of the Extended Ly α Emissionmentioning
confidence: 99%
“…forming galaxies at redshifts 3 ≤ z ≤ 6 in the Hubble Deep Field South and other regions (Wisotzki et al 2016;Leclercq et al 2017Leclercq et al , 2020Bielby et al 2020). Extended Lyα halos have also shown kinematic signs, suggesting large-scale rotation of accreting material (Prescott et al 2015) and a filamentary structure (Cantalupo et al 2014;Vernet et al 2017;Martin et al 2019;Umehata et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Bielby et al (2019) studied the association of O VI absorbing gas with galaxies at z < 1.4 using such a grism survey. Initial results from complete and deep galaxy surveys using IFU and grism observations around quasars with high-quality spectra have shown that neutral hydrogen and metal absorption can arise in a variety of galaxy environments (Bielby et al 2019(Bielby et al , 2020Fossati et al 2019b;Chen et al 2020a;Lofthouse et al 2020;Beckett et al 2021;Lundgren et al 2021;Muzahid et al 2021).…”
mentioning
confidence: 99%